Small-scale texture mapping - Kinnunen, Matti (2018)
This master’s thesis examines the applicability of texture mapping in modeling small-scale surface features of materials in computer graphics. A technique is introduced, implemented and examined using a custom software renderer. This technique uses sampled small-scale albedo, normal, and displacement maps to model complex small-scale surface features and their effect on surface reflectance. The implementation of the technique was able to model these features, but further improvements on the technique are needed to address the visual accuracy and computational efficiency.